Social media analytics dashboard for academics and the decision-making process: A systematic literature review - Christensen, Line Lisberg; Khalid, Md Saifuddin (Proceedings of the International Conference on Networked Learning, 2018)
Our worlds have changed since the social media exploded, and it affects not only our social, everyday lives but also our academic endeavours. Now, academics can disseminate knowledge through social media platforms, created specifically for academics and for the public. Uses of social media are now analyzed for providing an overview of the impact of academic dissemination, might be termed as social media analytics for academics — a non-traditional statistical dashboard that include both citation impact metrics and webometrics of scientific publications. The analytics have potential to change the way researchers disseminate, choose study focus, research fields, and much more. Readers also could rely on the analytics in the selection process. However, along with the social media analytics, comes a need for new terminology and use of metrics to evaluate the impact of research articles. Online interaction metrics have evolved to become alternative bibliometric matrices, that view downloads, likes, shares, comments, and other similar online engagements as the indicators of impact. The impact evaluation no longer solely depends on citations, but on the various forms of engagement and activity surrounding an article. This systematic literature review attempts to uncover whether literature about dashboards on social media for academics exists. Also, whether any study has been conducted on the decision-making process that comes with the recent social media dashboards for academics. The literature review uncovered 11 texts of relevance to the topic, along with five pre-determined texts. In order to create a legible overview of the literature, a qualitative content analysis was conducted, coded with 21 themes, and merged into three categories: (1) Bibliometrics, social media analytics and alternative metrics for the reputation of academics, (2) Academics’ strategy for- and impact of dissemination and (3) Dashboard for Academics’ knowledge dissemination analytics. The study shows that no study exists about dashboards for social media for academics, nor is there a focus on the decision-making process. Thereby, a need to study dashboards on social media exist, because, not only will altmetrics on the dashboards provide authors with critical numerical information, but also create an opportunity for the readers to make decisions regarding academic work and academics. Authors will, at the same time, be able to make decisions on what to further investigate/study and how to make greater impact in the broader society than just readers of the bibliographic databases.